Characteristics of Chitosan from Chitin Deacetylation Using Different NaOH Concentration and Evaluation of Its Solubility in Liquid Smoke - Ahmad Budi Junaidi; Nurul Hikmah; Utami Irawati; Nawwal Hikmah; Taufiqur Rohman (Jurnal Sains dan Terapan Kimia, 2026)
This research aimed to determine the effect of chitosan characteristics produced from the deacetylation of chitin with various concentrations of NaOH on its solubility in liquid smoke. Chitin produced from rajungan shell raw materials was deacetylated using 40% NaOH (K40%), 50% (K50%), and 60% (K60%). The resulting chitosan was then measured of its degree of deacetylation (DD), molecular weight (BM), and solubility in liquid smoke. The results showed that K40% had a DD of 56.99%, K50% had a DD of 72.86% and a BM of 149.1 kDa, also K60% had a DD of 82.87% and a BM of 102.6 kDa. The solubility of chitosan in 10% liquid smoke indicated that K40% was not dissolved, K50% was almost completely dissolved, and K60% was completely dissolved.